Review of the Adequacy of the Fund's Precautionary Balances. (Policy Papers; Policy Paper ;, 2010)
The paper reviews the adequacy of the Fund's precautionary balances and proposes a more transparent and rules-based framework for adjusting the precautionary balance target through time. The framework seeks to provide sufficient flexibility to capture the main elements considered relevant by the Board in the past when setting the target and draws on approaches followed by other IFIs, adapted to the particular circumstances of the Fund.